The Impact of Customer Satisfaction Level on The Decision-Making Process on Customer Financing at The Baitul Mal Wa Tamwil UGT Sidogiri Blitar Branch - Sulchan, Moch (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The level of contentment in BMT Sidogiri is the driving force behind this research. It is important to bear in mind that other research has used various terms to characterize satisfaction levels. Still, it has not provided a specific definition of the level of satisfaction. The level of satisfaction significantly influences financing decision-making in this instance. The problem that this research aims to address is the impact of customer contentment on their financing decisions. The objective of the study is to investigate the impact of customer satisfaction on the decision-making process at Baitul Mal Wat Tanwil UGT Sidogiri Blitar. Quantitative research employs an associative approach in this investigation. Primary data was collected through the distribution of questionnaires in this study. Purposive sampling is employed in the sample data collection technique. In this investigation, 75 respondents were employed as samples. Validity and reliability testing, normality testing, and hypothesis testing comprise the data analysis methodology employed in this investigation. The analysis results indicate that customer financing decisions at Baitul Mal Wat Tanwil UGT Sidogiri Blitar are positively influenced by the level of satisfaction